Antibody or Anybody? Considering the Role of MRGPRX2 in Acute Drug-Induced Anaphylaxis and as a Therapeutic Target - Mackay, Graham A.; Fernandopulle, Nithya A.; Ding, Jie; McComish, Jeremy; Soeding, Paul F. (Frontiers in Immunology, 2021)
Acute anaphylaxis to small molecule drugs is largely considered to be antibody-mediated with immunogloblin E (IgE) and mast cell activation being key. More recently, a role for drug-reactive immunoglobulin G (IgG) with neutrophil activation has also been suggested, at least in reactions to neuromuscular blocking agents (NMBAs). However, the mast cell receptor MRGPRX2 has also been highlighted as a possible triggering mechanism in acute anaphylaxis to many clinically used drugs. Significantly, MRGPRX2 activation is not dependent upon the presence of drug-recognising antibody. Given the reasonable assumption that MRGPRX2 is expressed in all individuals, the corollary of this is that in theory, anybody could respond detrimentally to triggering drugs (recently suggested to be around 20% of a drug-like compound library). But this clearly is not the case, as the incidence of acute drug-induced anaphylaxis is very low. In this mini-review we consider antibody-dependent and -independent mechanisms of mast cell activation by small molecule drugs with a focus on the MRGPRX2 pathway. Moreover, as a juxtaposition to these adverse drug actions, we consider how increased understanding of the role of MRGPRX2 in anaphylaxis is important for future drug development and can complement exploration of this receptor as a drug target in broader clinical settings.